Synthesis and Characterizations of Zinc Oxide on Reduced Graphene Oxide for High Performance Electrocatalytic Reduction of Oxygen - Jiemei Yu; Taizhong Huang; Zhankun Jiang; Min Sun; Chengchun Tang (Molecules, 2018)
Electrocatalysts for the oxygen reduction (ORR) reaction play an important role in renewable energy technologies, including fuel cells and metal-air batteries. However, development of cost effective catalyst with high activity remains a great challenge. In this feature article, a hybrid material combining ZnO nanoparticles (NPs) with reduced graphene oxide (rGO) is applied as an efficient oxygen reduction electrocatalyst. It is fabricated through a facile one-step hydrothermal method, in which the formation of ZnO NPs and the reduction of graphene oxide are accomplished simultaneously. Transmission electron microscopy and scanning electron microscopy profiles reveal the uniform distribution of ZnO NPs on rGO sheets. Cyclic voltammograms, rotating disk electrode and rotating ring disk electrode measurements demonstrate that the hierarchical ZnO/rGO hybrid nanomaterial exhibits excellent electrocatalytic activity for ORR in alkaline medium, due to the high cathodic current density (9.21 × 10−5 mA/cm2), positive onset potential (−0.22 V), low H2O2 yield (less than 3%), and high electron transfer numbers (4e from O2 to H2O). The proposed catalyst is also compared with commercial Pt/C catalyst, comparable catalytic performance and better stability are obtained. It is expected that the ZnO/rGO hybrid could be used as promising non-precious metal cathode in alkaline fuel cells.